Post-partum reproductive function of F1 crossbred cows under smallholder management conditions in central highland of Ethiopia - Dawo, F.; Zerbini, E. (1999)
Post-partum reproductive function of 50 F1 crossbred (Boran X Friesian) cows under smallholder farms around Holetta were monitored using plasma progesterone concentrations and profiles to examine Ovarian activity of cows and accuracy of estrus detection. Experimental cows were observed for signs of estrus twice per day: early in the morning and late in the afternoon by farmers. Blood samples were collected once per week from all cows after day 30 post-partum until pregnancy was determined per rectum or till end of the experiment. A progesterone concentration of less than 1, between 1-2 and greater than 2ng/ml were considered as anestrus, luteal activity and mid luteal phase or conception, respectively. Short luteal phases were considered as luteal cycles less than 17 days. Irrespective of calving data, 60 percent of cows lacked ovarian activity. Normal ovarian activity was observed in 26 percent of cows, of which only one cow commenced ovarian activity and conceived in less than 90 days and three cows conceived between 128-180 days, while the remaining cows conceived more than 180 days post-partum. The median days to first estrus and conception were 273 and 299, respectively. A total of 27 estruses and 25 ovulations were observed during the 18 weeks of study period. Of these estruses, 76 percent were efficiently detected by farmers while 24 percent were either missed or silent. Short luteal phases were observed in 22 percent of the cows. There was significant association between short luteal phases and ovulations without estrus (p<0.01). Short luteal phases observed in this study were not a prerequisite of the establishment of normal ovarian cyclicity.